An Analysis of Leg Length and Vo2Max of Junior Athletes in Basketball and Volleyball: Analisis Panjang Tungkai dan Vo2Max pada Atlet Junior Cabang Olahraga Bola Basket dan Bola Voli - Tridinda Aprilia (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2022)
Increased sports achievements are inseparable from the role of the scientific approach. A person's body structure is determined by bones and muscles. High-bodied people automatically have a long bone structure and vice versa. Factors related to body structure, body posture, and genetic ability to move in particular are one of the determinants of success in achieving achievement. A good level of physical fitness is very helpful for athletes in maintaining their achievements, especially in taking physical tests. Athletes will be able to do optimal physical tests if they have excellent physical fitness. One that describes a person's physical fitness level is VO2Max. The length of the limbs or one part of the body posture can also affect the level of VO2max. This type of research is a quantitative research using data analysis techniques using correlation analysis techniques and coefficient analysis of determination with the method used, namely descriptive. The number of samples in this study was 69 people. Consists of 41 basketball junior athletes and 28 volleyball junior athletes. Based on the results of the data analysis shows the magnitude of the correlation coefficient between the length of the leg and the VO2Max is (r = 0.28409). This it can be said that there is a strong correlation between the length of the leg and the VO2Max. From the results above, it can be determined that the limit of the leg length to the VO2Max is 8%. Keywords: VO2max, bone structure, stiffness